2021
DOI: 10.1177/10760296211012094
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Hemostatic Abnormalities Using a CWA-Small Amount Tissue Factor Induced FIX Activation Assay in Major Orthopedic Surgery Patients

Abstract: We analyzed the utility for a clot waveform analysis (CWA) of small tissue factor induced FIX activation (sTF/FIXa) assay in patients with major orthopedic surgery (including total hip arthroplasty [THA] and total knee arthroplasty [TKA]) receiving edoxaban for the prevention of venous thromboembolism (VTE). The sTF/FIXa assay using recombinant human TF in platelet-rich plasma (PRP) and platelet-poor plasma (PPP) was performed using a CWA in the above patients to monitor the efficacy of edoxaban administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The prolongation of peak times in patients with malignant neoplasm reflect with anticoagulants. The prolongation of peak time in CWA-APTT and sTF/FIXa due to anticoagulant were previously reported in major orthopedic surgery [17]. The peak time CWA-APTT or -sTF/FIXa may reflect with anticoagulant, and the peak height may reflect physiological clotting activity.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The prolongation of peak times in patients with malignant neoplasm reflect with anticoagulants. The prolongation of peak time in CWA-APTT and sTF/FIXa due to anticoagulant were previously reported in major orthopedic surgery [17]. The peak time CWA-APTT or -sTF/FIXa may reflect with anticoagulant, and the peak height may reflect physiological clotting activity.…”
Section: Discussionsupporting
confidence: 52%
“…Although elevated D-dimer is useful for detecting thrombosis in patients with cancer [14,15], there are no routine test for hypercoagulability. Recently, a clot waveform analysis (CWA) to activated partial thromboplastin time (APTT) has been developed to analyze to evaluate hemostatic abnormalities in patients with bleeding tendency and to monitor anticoagulant therapy [16,17]. Furthermore, the use of the small amount of TF induced FIX activation assay (sTF/FIXa) assay can evaluate the hemostatic abnormalities including platelet abnormalities [18].…”
Section: Introductionmentioning
confidence: 99%
“…This thrombin activates not only fibrinogen, but also FV, FVIII, FIX, FX, and FXI, with the activation cycle from thrombin to FXI continuing for a short time thereafter [ 14 ]. The CWA-sTF/FIXa with a 2000-fold diluted PT reagent (recombinant TF) [ 24 , 25 ] was developed to evaluate physiological coagulation, and was shown to be capable of measuring the FVIII concentration. As a cross-mixing test of the CWA-TT between calibration plasma and FVIII-deficient plasma showed a good dose-response curve, the CWA-TT may be able to measure the FVIII concentration.…”
Section: Discussionmentioning
confidence: 99%
“…However, most APTT reagents have some contact activation substance, and cannot demonstrate physiological coagulation [ 15 ]. Therefore, an sTF/FIXa assay [ 15 , 24 ] uses PRP as a physiological phospholipid instead of commercial APTT reagents. The CWA-TT also showed that the peak height, especially the 1st DPH-2, was higher in PRP than in PPP.…”
Section: Discussionmentioning
confidence: 99%
“…The clot waveform analysis (CWA)-APTT method [6] is capable of measuring very low coagulation factor VIII (FVIII) activities in hemophilia A [7] and to detect early disseminated intravascular coagulation (DIC) using biphasic waveforms [8]. Furthermore, CWA-APTT [6] is reported to be useful for the diagnosis of lupus anticoagulant, liver dysfunction, DIC, hemophilia, and factor VIII inhibitor [9][10][11][12], and for the monitoring of bypass therapy in patients who are positive for FVIII inhibitor or for anticoagulant therapy [13][14][15]. The CWA-APTT [6,15] and sTF/FIXa assays [5,14] are routine assays that are able to express the peak times and peak heights of the clotting curve or its derivative curve, easily when evaluating the thrombin burst.…”
Section: Introductionmentioning
confidence: 99%